Integrated groundwater use and management in vulnerable coastal zones of Asia-Pacific - Villholth, Karen G. (2013)
Groundwater in coastal zones around the globe is a critical asset in securing water, food and general development for millions of people. Particularly, in the Asia-Pacific region, such resources are significantly depended on in rural as well as urban areas for a wide range of uses, often as the only water source, which is exemplified by small island states. Present and future stresses on these significant, but often vulnerable systems, from human development, urbanization, climate change, and extreme events call for better understanding and awareness of these resources, their protection and best management approaches. The present chapter deals with the current level of knowledge of coastal groundwater systems in continental and island settings in the Asia-Pacific, their uses, vulnerabilities and hazards from various sources. The objective of the paper is to propose through an integrated framework approach how sustainable and resilient groundwater management can be promoted and enhanced. The work is partially based on the case of the tsunami in eastern Sri Lanka and the immense challenges but also opportunities it entailed for local and higher level groundwater management.